Grammatical Errors among University Students: Causes and Sustainability of Treatment - Mohamed Abo Elnour Abdel Mawla, Mostafa (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop the grammar level of undergraduate students through the basic skills of the Arabic language (listening, speaking, reading, writing), and that is by identifying the causes of grammatical errors among students of this stage, and discussing them through what we found them with grammatical errors reading, writing and speaking Listening to the lecture halls, duties and various assessments, they are from different Arab nationalities in a number of universities in the United Arab Emirates, and trying to avoid the causes of grammatical weakness by knowing them and developing appropriate solutions for them, in addition to monitoring the most common grammatical errors common to their use Daily and straighten, To open the way for researchers and scholars to study reading and writing weakness by identifying the manifestations of grammatical weakness and appropriate treatment methods and paying attention to teaching the Arabic language on modern scientific and pedagogical bases to develop its teaching and making intensive efforts to do so, as well as paying attention to monitoring the level of students and working to improve it and emphasizing educational developments that work to investigate the causes and phenomena and give it an accurate scientific explanation for the sustainability of classical Arabic among our children. The study adopts the descriptive analytical approach in addition to the semi-experimental approach, as the research is based on describing and analyzing students ’errors at the grammatical level as well as trying to remedy these problems and discuss their reasons for the sustainability of this treatment.